2011
DOI: 10.1063/1.3561766
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of ferromagnetism and superconductivity in Pb/PbO core/shell nanoparticles

Abstract: We report on the observations of spontaneous spin polarized moments in 7.4 nm Pb/PbO nanoparticles, which give rise to re-entrantlike temperature profiles for the magnetic susceptibility and magnetization in the superconducting phase that develops below 6.86 K. Results reveal the existence of a magnetic component below TC and superconductivity remains at low temperatures. A 30-fold increase in the critical magnetic field is also found. Superconductivity mainly arises from the 5 nm Pb core, whereas the 1.2 nm P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The use of borohydride reduction or polyol reactions provides some degree of shape control in nanoparticles of elemental superconductors [98]. Recently, colloidal synthesis has been employed to grow high quality monodispersed isolated Pb nanoparticles with a coreshell structure [99,100]. There are a number of reports on the growth of capped nanoparticles of superconductors such as MgB 2 , MgCNi 3 , Sn and Pb, showing ways to isolate individual particles from each other [101,102].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The use of borohydride reduction or polyol reactions provides some degree of shape control in nanoparticles of elemental superconductors [98]. Recently, colloidal synthesis has been employed to grow high quality monodispersed isolated Pb nanoparticles with a coreshell structure [99,100]. There are a number of reports on the growth of capped nanoparticles of superconductors such as MgB 2 , MgCNi 3 , Sn and Pb, showing ways to isolate individual particles from each other [101,102].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The neutron diffraction measurements in ferromagnetic superconductors ErRh 4 B 4 10 , HoMo 6 S 8 11 and HoMo 6 Se 8 12 indicate an inhomogeneous magnetic order coexisting with superconductivity. More recently, coexistence of these seemingly exclusive states was also seen in Pb/PbO core/shell nanoparticles 13 , and in two-dimensional interfaces between perovskite band insulators LaAlO 3 and SrTiO 3 14,15 .…”
Section: Introductionmentioning
confidence: 92%
“…25 Hsu et al reported superconducting Pb/PbO nanoparticles with a Pb core of 5 nm and a PbO layer of 1.2 nm. 26 Recently, a Pb/PbO compound confined in mesoporous carbon (OMC) was used as electrocatalysts for the electroreduction of CO 2 to CO. 27 Furthermore, reports on synthesizing nanocomposites of porous materials or zeolites with lead or lead oxides are limited. Dapurkar SE reported preparing and characterizing metal oxide nanoparticles, including PbO nanoparticles within the mesoporous channels of silicate molecular sieves MCM-41 and MCM-48.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hsu et al. reported superconducting Pb/PbO nanoparticles with a Pb core of 5 nm and a PbO layer of 1.2 nm . Recently, a Pb/PbO compound confined in mesoporous carbon (OMC) was used as electrocatalysts for the electroreduction of CO 2 to CO …”
Section: Introductionmentioning
confidence: 99%